PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT. BANK CAPITAL INDONESIA PERIODE TAHUN 2013 – 2022 - Yuliyani, Sulis; Lisdawati (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of the Rate of Return Ratio Assets and debt to share price ratio at PT Bank Capital Indonesia Tbk for the 2013-2022 period partially and simultaneously. The research method used is a quantitative approach. The population used in this research is the financial position report and profit and loss financial report of PT Bank Capital Indonesia Tbk 2013-2022. The sample used is the return on assets ratio, debt ratio, share price of PT Bank Capital Indonesia Tbk. The data analysis technique used is descriptive analysis and statistical analysis through the SPSS calculation stage using IBM SPSS version 24 (classical assumption test, regression analysis, coefficient test and hypothesis test). The research results show that Return On Assets has negatively a significant effect on stock prices, T Test calculation results obtained tcount of 3.201> 0.7063 ttable and a significant value of 0.015<0.05, the Debt To Equity ratio has positively a significant effect on share prices. The results of the T test calculation obtained tcount of 4.976> 0.7063 and a significant value of 0.002<0.05, ratio Debt To Equity Ratio has a significant influence on stock prices. The results of research simultaneously using the F test Retun On Assets and Debt To Equity Ratio simultaneously have an influence on shares. This is proven by the results of the F test calculation which shows Fcount 20,100>Ftable 4.46 and a significant value of 0.001 < 0.05